2012
DOI: 10.4028/www.scientific.net/amr.524-527.883
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pyrolysis Temperature on the Gaseous Products of Lignite

Abstract: Temperature-programmed pyrolysis of SL-lignite from Xilinhaote was investigated. The solid and gaseous pyrolysates were analyzed by means of gas chromatography(GC) and X-ray diffraction(XRD). The weight percents of surface moisture, ash, C, H and S increase with increasing the pyrolysis temperature in solid pyrolysates, while the volatile matter is contrary. The cracking reaction occurs before 600°C, the consolidation reaction happens between 600°C and 650°C, while the polycondensation or secondary reaction ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Similar with the first route, studies on this aspect are still at the beginning stage, and more focus should be paid. Recently, we conducted some attempts on the direct use of LRCs or their derivatives without complex separation. Humic acid (HA) mixtures extracted from LRC (typical lignite) by a diluted NaOH solution under mild conditions could be directly used to prepare Zr-based catalysts via the interaction of Zr 4+ with the acidic groups in HA, and the catalyst showed high efficiency for the conversion of biomass-derived furfural or ethyl levulinate. , Further studies showed that the raw lignite could be used directly to construct a Zr-based catalyst by a similar route, and the pretreatment of demineralization via acid washing of lignite could improve the stability of the obtained catalyst . These previous studies identified that the idea of the direct use of HA mixtures from lignite without separation and purification to construct a catalyst was feasible.…”
Section: Introductionmentioning
confidence: 99%
“…Similar with the first route, studies on this aspect are still at the beginning stage, and more focus should be paid. Recently, we conducted some attempts on the direct use of LRCs or their derivatives without complex separation. Humic acid (HA) mixtures extracted from LRC (typical lignite) by a diluted NaOH solution under mild conditions could be directly used to prepare Zr-based catalysts via the interaction of Zr 4+ with the acidic groups in HA, and the catalyst showed high efficiency for the conversion of biomass-derived furfural or ethyl levulinate. , Further studies showed that the raw lignite could be used directly to construct a Zr-based catalyst by a similar route, and the pretreatment of demineralization via acid washing of lignite could improve the stability of the obtained catalyst . These previous studies identified that the idea of the direct use of HA mixtures from lignite without separation and purification to construct a catalyst was feasible.…”
Section: Introductionmentioning
confidence: 99%
“…The SL-C produced more CH 4 than the other four chars. For the SL-C char, there may remain insufficiently decomposed alkyl groups on the aromatic macromolecular structure, and such functional groups are cleaved during the heat-up to 700 ℃, contributing to the formation of CH 4 [8,9].…”
Section: Gas Compositionmentioning
confidence: 99%